UHRF2 promotes intestinal tumorigenesis through stabilization of TCF4 mediated Wnt/β‐catenin signaling. Issue 8 (22nd May 2020) - Li, Liang; Duan, Qiuhui; Zeng, Zhiyang; Zhao, Jindong; Lu, Jiawei; Sun, Jialiang; Zhang, Jiqin; Siwko, Stefan; Wong, Jiemin; Shi, Tieliu; Zhang, Xueli; Liu, Mingyao; et al.
Abstract: Intestinal tumors mainly originate from transformed crypt stem cells supported by Wnt signaling, which functions through downstream critical factors enriched in the intestinal stem/progenitor compartment. Here, we show Uhrf2 is predominantly expressed in intestinal crypts and adenomas in mice and is transcriptionally regulated by Wnt signaling. Upregulated UHRF2 correlates with poor prognosis in colorectal cancer patients. Although loss of Uhrf2 did not affect intestinal homeostasis and regeneration, tumor initiation and progression were inhibited, leading to a markedly prolonged life span in Uhrf2 null mice on an Apc Min background. Uhrf2 deficiency also strongly reduced primary tumor organoid formation suggesting impairment of tumor stem cells. Moreover, ablation of Uhrf2 suppressed tumor cell proliferation through downregulation of the Wnt/β‐catenin pathway. Mechanistically, Uhrf2 directly interacts with and sumoylates Tcf4, a critical intranuclear effector of the Wnt pathway. Uhrf2 mediated SUMOylation stabilized Tcf4 and further sustained hyperactive Wnt signaling. Together, we demonstrate that Wnt‐induced Uhrf2 expression promotes tumorigenesis through modulation of the stability of Tcf4 for maintaining oncogenic Wnt/β‐catenin signaling. This is a new reciprocal feedforward regulation between Uhrf2 and Wnt signaling in tumor initiation and progression. Abstract : What's new? UHRF2 has been shown to be enriched in intestinal stem cells and upregulated in colorectal cancer. However, the role of UHRF2 in intestinal homeostasis and tumorigenesis has not been explored in vivo. This study shows that Uhrf2 is expressed in mouse intestinal crypts and adenomas and is transcriptionally regulated by Wnt signaling. Uhrf2 further maintains oncogenic Wnt/β−catenin signaling through modulation of Tcf4 protein stability to enhance the stemness and tumorigenicity of intestinal progenitors. The findings reveal reciprocal feedforward regulation between Uhrf2 and Wnt signaling in tumor initiation and progression, and highlight Uhrf2 as a potential therapeutic target in colorectal cancer.